Exploring Pharmaceutical Personnel’s Insight and Attitudes Toward Complementary and Alternative Medicine: Preferences for Common Cold Remedies - Maheni, Ni Putu Asri Dewi; Ardinata, I Putu Riska; Rudiartha, I Gusti Lanang Made; Widowati, I Gusti Ayu Rai (Bali Medical and Wellness Journal, 2025)
Background: Pharmaceutical personnel are responsible for providing accurate advice and therapeutic options to ensure safe and effective treatments. Insufficient knowledge of medications can lead to inappropriate drug selections, adversely affecting patient outcomes. Objectives: This study aims to assess the knowledge of pharmaceutical personnel regarding complementary and alternative medicine (CAM) and their preferences for remedies used to treat the common cold. Method: A cross-sectional design was utilized, involving 35 respondents from selected chain pharmacies. Data were collected using a validated questionnaire that included the Guttman scale for knowledge assessment and the Likert scale for evaluating attitudes and behaviors. Descriptive analysis was performed using SPSS. Results: Most respondents were aged 17-25 years (60.0%), predominantly female (94.3%), held a diploma degree (65.7%), had a monthly income between 2.5-5 million rupiah (74.3%), and had less than three years of work experience (68.6%). Notably, 60.0% had not received training in CAM. The findings indicated that 54.3% of respondents had adequate knowledge of CAM, and 68.6% displayed a positive attitude toward selecting common cold remedies. Additionally, 62.9% recommended supplements or herbal products to patients for preventing or treating the common cold and provided guidance on their proper use. Conclusion: To enhance their knowledge and ensure evidence-based recommendations, pharmaceutical personnel could benefit from additional training on CAM. Furthermore, ongoing education about safe and effective cold remedies may improve patient care and promote better decision-making.